Evolution of Copper Homeostasis and Virulence in Salmonella - Méndez, Andrea A. E.; Mendoza, Julián I.; Echarren, María Laura; Terán, Ignacio; Checa, Susana K.; Soncini, Fernando C. (Frontiers in Microbiology, 2022)
Salmonella enterica sv. Typhimurium modulates the expression of factors essential for virulence contributing to its survival to the surge of copper (Cu) in the SCV (Salmonella containing vacuole). This bactericidal host innate immune component primary targets the bacterial envelope, where most cuproproteins are localized. While in most enteric species periplasmic Cu homeostasis is maintained by the CusR/CusS-controlled CusCFBA efflux system encoded in the cus locus, we noticed that these genes were lost from the Salmonella core genome. At the same time, Salmonella acquired cueP, coding for a periplasmic Cu-chaperone. As cus, cueP was shown to be essential for bacterial survival in a copper-rich environment under anaerobiosis, suggesting that it can functionally substitute the CusCFBA system. In the present study, the whole E. coli cus locus was reintroduced to the chromosome of the Salmonella wild-type or the ΔcueP strain. While the integrated cus locus did not affect Cu-resistance under aerobic conditions, it increases Cu tolerance under anaerobiosis, irrespective of the presence or absence of cueP. In contrast to the Cus system, CueP expression is higher at high copper concentrations and persisted over time, suggesting separate functions. Finally, we observed that, regardless the presence or absence of cus, a mutant deleted of cueP shows a deficiency in replication inside macrophages compared to the wild type strain. Our results demonstrate that CueP and CusCFBA exert redundant functions for metal resistance, but not for intracellular survival and therefore for the virulence of this pathogen.